Pediatric Acute Promyelocytic Leukemia: Epidemiology, Molecular Features, and Importance of GST-Theta 1 in Chemotherapy Response and Outcome - Andrade, Francianne G.; Feliciano, Suellen V. M.; Sardou-Cezar, Ingrid; Brisson, Gisele D.; Santos-Bueno, Filipe V. dos; Vianna, Danielle T.; Marques, Luísa V. C.; Terra-Granado, Eugênia; Zalcberg, Ilana; Santos, Marceli de O.; Costa, Juliana T.; Noronha, Elda P.; et al. (Frontiers in Oncology, 2021)
Previous studies have suggested a variation in the incidence of acute promyelocytic leukemia (APL) among geographic regions with relatively higher percentages in the Latin American population. We aimed to explore the population burden of pediatric APL, gathering the information from population-based cancer registry (PBCR) and the APL diagnosis obtained throughout incident cases from a hospital-based cohort. The homozygous deletion in glutathione S-transferases (GSTs) leads to the loss of enzyme detoxification activity, possibly affecting treatment response. Mutations in the RAS pathway genes are also a key component of the disease both in pathogenesis and outcomes. We have assessed mutations in the RAS-MAP kinase pathway (FLT3, PTPN11, K-/NRAS) and GST variant predisposition risk in the outcome. Thirty-five APL cases (4.3%) were registered in the PBCR out of 805 AML cases in children and adolescents. The age-adjusted incidence rate was 0.03 per 100,000 person-years. One-hundred sixty-three APL patients were studied out of 931 AML cases (17.5%) from a hospital-based cohort. Mutations in FLT3, KRAS, and NRAS accounted for 52.1% of cases. Patients with APL presented a 5-year probability of overall survival of 67.3±5.8%. GSTT1 null genotype conferred adverse prognosis, with an estimated hazard ratio of 2.8, 95% confidence interval 1.2-6.9. We speculate that the GSTT1 polymorphism associated with therapeutic and would allow better overall survival of APL patients with GSTT1 null genotype.”.